The mediating role of early maladaptive schemas and parenting styles on the relationship between insecure attachment and anxiety among adolescent students of international secondary schools in Kelang Valley, Malaysia / Seyed Ebrahim Mousavi - Seyed Ebrahim, Mousavi (2016)
Anxiety is among the most prevalent forms of psychopathology in adolescence. Both the attachment and cognitive theories emphasize the role of the quality of the parent-child relationship in psychopathology and its impact on emotional health. Whereas few studies have examined the additive and reciprocal effects of multiple factors on the development of anxiety symptoms in adolescents, the present study was an attempt to examine the influence and the reciprocal connections of three sets of variable including attachment style, parental behaviors rearing and cognitive schemas on the development of anxiety. Importantly, this was also the first study to examine the mediating role of early maladaptive schemas and parenting variables in the links between insecure attachment and anxiety symptoms in an adolescent sample with four cultural backgrounds (Malaysian, Arab, Indian and American/European). Using multiple cluster sampling, 38 classrooms from 13 international secondary schools in Kuala Lumpur, Malaysia were selected. A sample of 762 non-clinical adolescents (302 girls and 460 boys) aged 13-18 years (mean age = 15.37 years) completed the questionnaires measuring attachment (ASQ), perceived parenting behaviors (EMBU-C), early maladaptive schemas (YSQ-S3) and anxiety symptoms (SCAS). The results indicated that there were small to moderate positive correlations among various risk factors, with regression analyses revealing insecure attachment, two parenting styles (Anxious Rearing and Rejection) and six particular EMSs were accounted as significant predictors of anxiety in adolescents. Further, the findings revealed that cognitive maladaptive schemas within Impaired Autonomy and Overvigilance/Inhibition schema domains were stronger predictors of anxiety compare to attachment and parenting variables. The findings as well indicated the strong correlation between parenting behaviors and maladaptive cognitive schemas. Particularly, high parental rejection and low parental warmth were strongly associated with Disconnection and Rejection domain as well as parental overprotection and anxious rearing with Impaired Autonomy schema domain. Furthermore, investigation of cultural differences revealed that Asian samples (Malaysian, Arab and Indian) considerably reported the higher rate of anxiety symptoms than European/American sample as well as on almost all measured risk factors. Further, Malaysian adolescents reported the highest level of anxiety symptoms. The results also indicated some differences between Malaysian three ethnic groups on the measures of study. Finally, the finding suggests that adolescents with insecure avoidance attachment who perceived their parents’ behaviors characterized by rejection and anxious rearing are at greater risk for increased anxiety symptoms. Further, particular early maladaptive schemas and parenting style do mediate the relations between insecure attachment and anxiety in the adolescent.